Influenza pattern analysis system through mining weblogs - Khoo, Pei Lin *; Lee, Yunli * (World Academy of Science, Engineering and Technology, 2012)
Weblogs are resource of social structure to discover and track the various type of information written by bloggers. In this paper we proposed to use mining weblogs technique for identifying the trends of influenza where blogger had disseminated their opinion for the anomaly disease. In order to identify the trends, web crawler is applied to perform a search and generated a list of visited links based on a set of influenza keywords. This information is used to implement the analytics report system for monitoring and analyzing the pattern and trends of influenza (H1N1. Statistical and graphical analysis reports are generated. Both types of the report have shown satisfactory reports that reflect the awareness of Malaysian on the issue of influenza outbreak through blogs.